2004
DOI: 10.1007/s00340-004-1497-3
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the super-enhanced light transmission through a 2-D metallic annular aperture array: a study of photonic bands

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
100
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(106 citation statements)
references
References 16 publications
4
100
1
1
Order By: Relevance
“…There is a renewed interest in electromagnetic FP resonances, especially their relevance to the recently observed transmission enhancement through subwavelength openings in normally opaque objects, [1][2][3][4][5][6][7][8] as well as to the ensuing debate on the relative contributions of surface wave versus diffraction in such phenomena. [9][10][11][12][13][14][15][16][17][18][19] It has been shown that light transmission through hole arrays in perfect-conductor thin films, where there can be no true surface waves, may be attributed ͑via Babinet's principle͒ to the reflection by the complementary structure consisting of planar arrays of perfect-conductor disks. 17,18 Transmission can always reach unity at some resonant wavelengths regardless of how small the holes are, while the complementary system can exhibit perfect reflection for arbitrarily small disks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a renewed interest in electromagnetic FP resonances, especially their relevance to the recently observed transmission enhancement through subwavelength openings in normally opaque objects, [1][2][3][4][5][6][7][8] as well as to the ensuing debate on the relative contributions of surface wave versus diffraction in such phenomena. [9][10][11][12][13][14][15][16][17][18][19] It has been shown that light transmission through hole arrays in perfect-conductor thin films, where there can be no true surface waves, may be attributed ͑via Babinet's principle͒ to the reflection by the complementary structure consisting of planar arrays of perfect-conductor disks. 17,18 Transmission can always reach unity at some resonant wavelengths regardless of how small the holes are, while the complementary system can exhibit perfect reflection for arbitrarily small disks.…”
Section: Introductionmentioning
confidence: 99%
“…Inside the subwavelength openings, either in slit [11][12][13][14] or annular geometry, 15 standing wave patterns are formed along the longitudinal direction, giving rise to FP resonances.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Such nanostructures provide additional functionalities compared to simple circular apertures in terms of very high absolute transmission related to specific waveguided modes in annular apertures, absent in simple circular holes. Coupled to surface plasmon polariton modes on metal film interfaces, these modes provide a possibility to achieve high transmission, field enhancement as well as high extraction efficiency of light trapped in the substrates.…”
mentioning
confidence: 99%
“…There have been studies considering AAA with glass as a substrate, in the near-infrared, and the visible regime. [1][2][3][4][5][6] Recently, it was experimentally demonstrated an enhanced transmission around 90%. 9 When glass is used a substrate, it is possible to take advantage of the resonance associated with the cutoff of the TE 11 mode of individual annular apertures.…”
mentioning
confidence: 99%
“…Several theories [4,5] and experiments [6][7][8] have been carried out to understand and optimize this phenomenon. The origin of this extraordinary transmission changes depending on the shape of the apertures.…”
mentioning
confidence: 99%